2018
DOI: 10.1088/1361-6668/aab8dd
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Cu–Sn mixing so as to enable higher critical current densities in RRP®Nb3Sn wires

Abstract: Dipole magnets for the proposed Future Circular Collider (FCC) demand specifications significantly beyond the limits of all existing Nb 3 Sn wires, in particular a critical current density (J c ) of more than 1500 A mm −2 at 16 T and 4.2 K with an effective filament diameter (D eff ) of less than 20 μm. The restacked-rod-process (RRP ® ) is the technology closest to meeting these demands, with a J c (16 T) of up to 1400 A mm −2 , residual resistivity ratio>100, for a subelement size D s of 58 μm (which in RR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 40 publications
2
35
0
Order By: Relevance
“…31, while the orange dashed lines are for the best Ti-doped RRP® after the optimized Cu-Sn mixing heat treatment of ref. 8. Our Nb4Ta wire has a layer Jc of 3210 ± 920 A/mm 2 at 12 T and 1250 ± 360 A/mm 2 at 16 T, values typical of those found for Ta-doped RRP® conductors, which range between 3190-5250 A/mm 2 at 12 T and 1400-1880 A/mm 2 at 16 T. The Tidoped RRP® conductor after optimized heat treatment has markedly better 16 T properties, with a layer Jc > 2000 A/mm 2 .…”
Section: Magnetization Characterizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…31, while the orange dashed lines are for the best Ti-doped RRP® after the optimized Cu-Sn mixing heat treatment of ref. 8. Our Nb4Ta wire has a layer Jc of 3210 ± 920 A/mm 2 at 12 T and 1250 ± 360 A/mm 2 at 16 T, values typical of those found for Ta-doped RRP® conductors, which range between 3190-5250 A/mm 2 at 12 T and 1400-1880 A/mm 2 at 16 T. The Tidoped RRP® conductor after optimized heat treatment has markedly better 16 T properties, with a layer Jc > 2000 A/mm 2 .…”
Section: Magnetization Characterizationsmentioning
confidence: 99%
“…To achieve such not yet achieved dipole fields requires magnet conductors with the not yet achieved high current density (Jc) of 1500 A/mm 2 at 16 T (4.2 K), while simultaneously maintaining high Cu stabilizer residual resistivity ratio (RRR) ≥ 100 and a large strand diameter of order 1 mm [7]. Recent rethinking of the heat treatment of commercial rod restack process (RRP) conductors has shown that a better optimized Sn mixing heat treatment can allow Jc (16 T, 4.2 K) as high as 1300 A/mm 2 in specially selected 0.8 mm diameter wires, a significant 20% increase over the best prior standard heat treatment [8]. However, real conductor production has significant spread so there is little hope to achieve FCC specification by this route alone.…”
Section: Introductionmentioning
confidence: 99%
“…This deserves a study of its own to supplement the results presented here. Effects on the allowable HT window of a simplified HT scheme that has two stages (instead of three) to control the Sn-Nb-Cu Nausite phase are also worthy of a systematic study 19 .…”
Section: Resultsmentioning
confidence: 99%
“…Reducing the size of Nb 3 Sn sub-elements can mitigate these instabilities significantly, and a sub-element size around 20 μm or less is desirable 1 . However, size reductions below 50 μm in RRP wires have resulted in a dramatic drop of J c 8,19 . In addition, such wires still need further development to become technological conductors that can be readily fabricated in piece-lengths sufficient for applications.…”
Section: Introductionmentioning
confidence: 99%
“…An important recent contribution was the reassessment of heat treatment design for Restacked Rod Process (RRP ® ) wires (Bruker OST) undertaken by Sanabria et al [2], [3]. Conventional heat treatments include steps at around 210 °C and 400 °C, followed by the reaction step that forms Nb3Sn at 650-665 °C (Fig.…”
Section: Introductionmentioning
confidence: 99%